When the population of an endangered marine mollusc (Patella ferruginea) increases almost three-fold in ten years. Reality or fiction? - Ostalé-Valriberas, E.; Sabino-Lorenzo, Á.; Ali-Ahmed, A.; Pavón-Paneque, A.; Sempere-Valverde, J.; Espinosa, F.; García-Gómez, J. C. (Frontiers in Marine Science, 2023)
The critically endangered species Patella ferruginea (Gastropoda, Patellidae), endemic to the western Mediterranean, has breeding populations in both natural and artificial habitats, the latter of which are generally linked to port infrastructures. Over the past decade, the temporal change of this species’ population has been monitored (structure and density) using exhaustive censuses along Ceuta’s coast (Strait of Gibraltar), one of the few stronghold populations within the entire Mediterranean basin. This study focuses on the population dynamics of P. ferruginea in Ceuta and the environmental factors that affect the structure of this population, such as wave exposure, coastline heterogeneity, substratum roughness, substratum lithology, and chlorophyll-a concentration. Different potential negative interactions were also considered: angling, shell fishing, bathing in the intertidal, bathing near the intertidal, recreational boating and temporary migrant campsites nearby. The results have shown in the period 2011-2021, the estimated size of P. ferruginea population has increased by 200 %, from 55,902 to 168,463 individuals (of which 131,776 are adults). The subpopulation with the greatest increase in these years was the one settled on dolomitic rip-raps inside the Ceuta’s harbor, with an increase of 1,288%. The results of the present study indicate that Ceuta hosts the main population of this endangered species through its distributional range (Western Mediterranean), being a source population on the Southern Iberian Peninsula that its preservation must be prioritized. Statistical modelling has shown that the adult density of P. ferruginea is positively influenced by coastal heterogeneity, habitat area and substratum roughness, but negatively by vertical inclination, concentration of chlorophyll-a, and anthropogenic impact. These results also support the concept of ¨Artificial Marine Micro-Reserves¨ as a new area-based conservation measure according with the IUCN guidelines, as these will contribute to setting up a network of these source populations that promote genetic flow among populations, with eventual recolonization throughout its original distribution.